2016
DOI: 10.5194/jsss-5-381-2016
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a sensor for a Tian–Calvet calorimeter with LTCC-based sensor discs

Abstract: Abstract. In this work, it is shown how a finite element method (FEM) model of a Tian-Calvet calorimeter is used to find improvements in the sensor design to increase the sensitivity of the calorimeter. By changing the layout of the basic part of the sensor, which is a low temperature co-fired ceramics (LTCC) based sensor disc, an improvement by a factor of 3 was achieved. The model was validated and the sensors were calibrated with a set of measurements that were later used to determine the melting enthalpies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…The results of T m−In = 429.66 K, Δ fus H −In = 3.42 kJ/mol and T m−Zn = 692.77 K, Δ fus H −Zn = 7.28 kJ/mol. The T m and Δ fus H of zinc determined by DSC8000 were very close to those in references (for indium, T m−In = 429.7545 K, 14 429.7485 K; 15 Δ fus H −In = 3.45 kJ/mol, 14 3.28 kJ/mol; 16 and for zinc, T m = 692.65 K, 17 696 K, 18 692.81 K; 19 Δ fus H −Zn = 7.30 kJ/mol, 18 7.32 kJ/mol 19 ). This demonstrated that the accuracy of the DSC instrument was reliable.…”
Section: Dsc Measurement Of Inasupporting
confidence: 86%
“…The results of T m−In = 429.66 K, Δ fus H −In = 3.42 kJ/mol and T m−Zn = 692.77 K, Δ fus H −Zn = 7.28 kJ/mol. The T m and Δ fus H of zinc determined by DSC8000 were very close to those in references (for indium, T m−In = 429.7545 K, 14 429.7485 K; 15 Δ fus H −In = 3.45 kJ/mol, 14 3.28 kJ/mol; 16 and for zinc, T m = 692.65 K, 17 696 K, 18 692.81 K; 19 Δ fus H −Zn = 7.30 kJ/mol, 18 7.32 kJ/mol 19 ). This demonstrated that the accuracy of the DSC instrument was reliable.…”
Section: Dsc Measurement Of Inasupporting
confidence: 86%